Overcoming two technical pitfalls in MRI of paediatric and adolescent sacroiliitis. Issue 3 (March 2019) - Orr, K.E.; Andronikou, S.; Bramham, M.J.; Holjar-Erlic, I.; Menegotto, F.; Ramanan, A.V.
Highlights: Poor MRI positioning makes MRI of the sacroiliac joints more difficult to interpret. Findings related to skeletal immaturity can lead to overdiagnosis of sacroiliitis. Optimal positioning of sacroiliac joint MRIs helps to avoid false positive diagnosis of erosions. Knowing the appearance of haematopoetic marrow can avoid misdiagnosis of sacroiliitis on MRI.